G30S dan Tahanan Politik dalam Karya John Roosa: Studi Historiografi - Mitha Arisetya; Hendra Naldi (PAMA Aksara, 2023)
This article describes G30S and Political Prisoners in the book by John Roosa. The purpose of this study is to describe the events of G30S and political prisoners. This study uses historical methods in its writing, namely heuristics, verification, interpretation and historiography. The results of this study illustrate that G30S is a movement origaniting from the internal Army and the Special Bureau, which is one of the bodies the PKI created by Aidit to prevent a coup that will be caried out by the Council of Generals. G30S resulted in the killing of hundreds thousands people and the arrests of millions. Political prisoners living in utilization sites and camps were subjected to various forms of torture and abuse. The release of political prisoners began in the 1970`s. Propaganda and historical engineering carried out by the New Order meant that political prisoners were never part of memory and forgetten. John Roosa gave his thoughts and analysis of G30S as a reference for understanding G30S and how this incident was used as pretext for the killing and detention of PKI members.